Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen di Kedai Kopi Soedjenk Kota Bengkulu - Siti Yuningsih; Samsul Akmal; Rijalul Fhikri (STIA Bengkulu, 2026)
The purpose of this study, among others, to determine the effect of product quality on consumer satisfaction at the Soedjeng Coffee Shop, Bengkulu City. This research is quantitative research. The population in this study were all consumers of the Bengkulu City Soedjenk coffee shop. The sample used in this study were 60 people. In this study, researchers used data collection methods by means of observation, interviews and distributing q`uestionnaires. Further data analysis used a simple linear regression analysis instrument test, coefficients, determination, and also hypothesis testing. The results of this study indicate that product quality has a positive and significant effect on consumer satisfaction.